(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
Waste PVC parts and waste rubber materials are used to improvise a pressure switch. Also, metallic parts are involved in building that pressure switch. The design of pressure switch considers the using of cheap waste materials and involves so simple design that any primitive technic can build this item. Furthermore, the design of pressure switch puts into considerations the hazard associated with rubber’s diaphragm leakage or failure. The dimensions of switch’s parts are selected based on computation using finite element analysis for the two pieces of rubber which are synchronously working. The first rubber piece works as a diaphragm while the second, which is strip, works as spring as well as adjustable tensioner to regulate the set value of pressure. There are two metallic parts working on transferring the motion from the diaphragm to strip. The first metallic part is spindle and the second is the leverage which is connected to the electrical contact too. The two rubber pieces and the two metallic parts are drawn in Catia R17 software, then they are imported to Ansys Workbench 2022 software where a three dimensional modeling is created. The purpose of this modeling is to find out the relation between the applied pressure on the diaphragm and the resulting deformation on the strip which is previously stretched to corresponding certain value of pressure. Depending on the results obtained from the modeling, a real pressure switch is built with the same dimensions in modeling. Then, that real pressure switch is tested using the same input pressure values in the modeling. The practical deformation values are compared to the corresponding values obtained from the Ansys Workbench 2022 modeling. The comparison shows that the experimental deformations are higher at lower pressure values because the mechanical properties of the old real rubber are degraded with time while at higher pressure vales the real deformations become less than those in the modeling because the friction in real joints increases with high pressure and also, in Ansys Workbench 2022 modeling, the friction in joints is neglected. Anyway, there is little difference in magnitudes of deformation but generally both practical and modeling results have the same behavior and manor besides they follow the same logical path.